Orthotopic ileal neobladder creation according to the original surgical method “Belgrade pouch” – A ten-years experience - Bančević, Vladimir; Aleksić, Predrag; Stamenković, Dušica (Vojnosanitetski pregled, 2021)
Background/Aim. The principle of continent urinary derivations is based on the formation of a reservoir as similar as native bladder is, with satisfactory capacity, high level of continence, low pressure and small resorbent surface as possible to prevent metabolic disorders. Methods. This prospective and partially retreospective study included 148 patients with organ confined muscle invasive bladder cancer, operated on in a ten-year period, and followed up in a 3-year period. After a radical cystectomy, an original surgical technique of creating “U” shaped orthotopic neobladder using a short ileal segment, average length of 30 cm, called “Belgrade pouch”, was performed. Results. The results of 126 male and 22 female patients, three years following the surgery, showed average pouch capacity of 477 (330–659) mL, insignificant residual urine of 52 (0–92) mL, and the averageurinary frequency was five times within 24 h. Day time continence was present in 90% of patients and nighttime continence in 88% of patients, 7% of patients had mild acidosis, and 3% of patients had vitamin B12 deficiency. Conclusion. The neobladder created according to the “Belgrade pouch“ technique showed excellent results comparabile with standard techniques, with adequate capacity, high continence rate, favourable 24 h voiding frequency, insignificant residual urine, and a significantly lower rate of metabolic complications during the 3 years of the follow-up period.